A Comparative Study of Astanga Hridaya and Astanga Samgraha - A Review Article. - Sewada, Deepak; Sharma, Mahendra; Mishra, Tribhuwan Nath; Arora, Pooja (International Research Journal of Ayurveda & Yoga, 2023)
Background: This study is an attempt to compile concept of mentioned in Vagbhatta Samhita i.e. Astanga Hridaya and Astanga Samgraha so that all the knowledge regarding could be comes under a platform. On the basis of evidences, it can be concluded that Astanga Samgraha and Astanga Hridaya were written by two different authors. Astanga Samgraha is written by Vridha Vagbhatta (500 AD) Astanga Hridaya is written by Laghu Vagbhatta (6th century). Both of these Acharya’s actually were related. Due to difference in time period; Astanga Samgraha is more influenced by the Sushruta Samhita while Astanga Hridaya is lineated towards Charaka Samhita. In both the Samhitas description of Sharira Rachana is found in Astanga Samgraha and Uttar Sthana. Material & Methods: The data used in current study was gathered from major Ayurvedic Samhitas, books based on historical background of Ayurveda, indexed – non indexed journals, widely dispersed research publications. Conclusion: This study reveals verity behind similarity and differences between Astanga Hridaya & Astanga Samgraha. The Time periods, Authors, language & style and some other subject matters of both the texts.